Evaluation of Protein Kinase C(β) and PPAR(γ) Activity in Diabetic Rats Supplemented with Momordica charantia - Chandru, Swetha (J Clin Diagn Res, 2016)
INTRODUCTION: The present study was taken up to compare and evaluate the effect of Momordica charantia supplementation with pioglitazone on PKC-β and PPAR-γ activity in kidneys of diabetic rats. The hypoglycaemic and lipid lowering effect of Momordica charantia were screened in laboratory animal model and its potency was compared with a Thiazolidinedione (TZD) group antidiabetic drug like pioglitazone. MATERIALS AND METHODS: Adult healthy albino rats of Wistar strain aged 3-4months, weighing between 170-250gm of either sex were divided into 4 groups; Group 1 (normal controls), Group 2 (diabetic controls), Group 3 (diabetic rats treated with pioglitazone) and Group 4 (diabetic rats treated with bitter melon juice). Type 1 Diabetes was induced in rats by intraperitoneal injection of streptozotocin at a dose of 55 mg/kg body weight, following which glucose levels were estimated by Accu chek- active glucometer on day 0, 7, 14, 21 and 28 days to assess the efficacy of Bitter Melon Juice (BMJ) and pioglitazone. After 28 days of treatment, the rats were sacrificed and blood collected from abdominal vena cava was used for estimation of triglycerides by Glycerol 3 phosphate oxidase phenol aminophenazone method and cholesterol by Cholestrol oxidase phenol aminophenazone method. PKC-β and PPAR-γ were estimated in the dissected kidneys by using double sandwich ELISA based kits on an automated plate reader. RESULTS: BMJ significantly reduced blood glucose levels in group 4 as compared to diabetic controls (p<0.001). Total cholesterol and triglycerides were significantly reduced in both group 3 and 4. In Group 4, there was reduction in PKC-β levels, when compared to Group 3(p=0.004). PPAR-γ levels were increased in both Group 3 and 4, when compared to Group 2. CONCLUSION: The results suggest that BMJ has hypoglycaemic and lipid lowering effect in diabetic animal models. BMJ increases PPAR-γ activity and decreases PKC-β activity in kidneys of diabetic rats, thereby preventing the complications of diabetes mellitus. Fresh BMJ mimics action of pioglitazone belonging to TZD group thus showing a potential for further research in identifying the active molecules responsible for glucose and lipid lowering action.